Factor Analysis of Causes and Solutions of Stunting Cases in Indonesia: Literature Review - Lubis, Dita Anggriani; Agustia, Dilma'aarij; Br Gultom, Ria Fazelita; Nainggolan, Wiwiek Elsada; Khoiriyah, Fitri; Hidayati, Yusmalia (Jurnal Mamangan, 2024)
Stunting is one of the Sustainable Development Goals (SDGs) targets included in the sustainable development goals, namely eliminating hunger and all forms of malnutrition by 2030 and achieving food security. Reducing the stunting rate by 40% by 2025 is the target set. Malnutrition, especially during the First 1000 Days of Life (HPK), can result in stunting. Stunting can impact motor and verbal development, increase degenerative diseases, morbidity and death. In addition, stunting can result in stunted growth and development of neuron cells, thereby affecting cognitive development in children. In this research, the method used is a literature study with a method of searching, combining essences and analyzing facts from several scientific sources that are accurate and valid. In the results of this research, we found articles regarding stunting prevention which stated that promotive and preventive efforts using various media and methods could influence knowledge, attitudes and even pregnant women regarding stunting prevention. Providing education in various methods and using it in various educational media can increase knowledge and attitudes and since pregnancy, behavior regarding stunting prevention can be implemented.